The Relationship between Islamic Religious Education Learning Outcomes and Commendation on Students - Haerudin,; Harmawati, (International Journal of Psychosocial Rehabilitation, 2020)
In this study aims to discuss and find out the relationship between PAI learning outcomes and commendable morals in grade IX students of Nurussalam Karawang Islamic Middle School. The research method used in this study is a quantitative research method with the type of correlation research. The population is all 120 Nurussalam Islamic Junior High School students and the sample is class IX students in the 2018/2019 academic year Nurussalam Islamic Junior High School, amounting to 60 people. The technique of collecting data uses the instrument of learning outcomes and the questionnaire of the laudable character of class IX students in 2018/2019 Islamic Nurussalam Middle School. Based on the results of the study showed a significant relationship between PAI learning outcomes with commendable morals in class IX students of Nurussalam Islamic Middle School, Karawang District with a strong closeness. This shows with the acquisition of the value of tcount is 7.966. The value of table with N = 60 at the error level of 5% is 2.002. Tcount> t table then Ho is rejected and Ha is accepted.